2017
DOI: 10.1364/oe.25.024281
|View full text |Cite
|
Sign up to set email alerts
|

Dual-band unidirectional reflectionless phenomena in an ultracompact non-Hermitian plasmonic waveguide system based on near-field coupling

Abstract: Dual-band unidirectional reflectionlessness and coherent perfect absorption (CPA) are demonstrated in a non-Hermitian plasmonic waveguide system based on near-field coupling between a single resonator and the resonant modes of two resonators showing an electromagnetically induced-transparency-like (EIT-like) effect. The non-Hermitian plasmonic system consists of three metal-insulator-metal (MIM) resonators coupled to a MIM plasmonic waveguide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…In 1998, Bender et al [1,2] discovered that non-Hermitian Hamiltonian with parity-time symmetry could have the real eigenvalue spectra. Further study of the non-Hermitian systems showed the existence of exceptional point (EP), where many interesting physical phenomena occur in classical optical systems [3][4][5][6][7][8][9][10][11][12][13], such as optical isolation [3], coherent perfect absorption [5], unidirectional reflectionlessness [8][9][10][11][12][13], electromagnetically induced transparency (EIT) [14], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, Bender et al [1,2] discovered that non-Hermitian Hamiltonian with parity-time symmetry could have the real eigenvalue spectra. Further study of the non-Hermitian systems showed the existence of exceptional point (EP), where many interesting physical phenomena occur in classical optical systems [3][4][5][6][7][8][9][10][11][12][13], such as optical isolation [3], coherent perfect absorption [5], unidirectional reflectionlessness [8][9][10][11][12][13], electromagnetically induced transparency (EIT) [14], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The data in some of the processes of elastic scattering such as nucleus-nucleus scattering [5] and electron scattering from solid crystals [6] fit better if one adopts complex potentials involving a nonpositive imaginary part. Moreover, according to the advancement of techniques for unfolding quantum theory, the necessity of quantum manipulation with complex potentials takes place in many different areas of physics and related topics such as optics [7][8][9][10][11], statistical physics [12,13], relativistic quantum field theory [14][15][16], nuclear physics [17], condensed matter physics [18][19][20], and biology [21]. To analyze the stability and nonlinear modes of optical beams propagating along an asymmetric waveguide, an imaginary potential has been adopted [11].…”
Section: Introductionmentioning
confidence: 99%
“…So far, unidirectional reflectionlessnesses have been proposed in some non-Hermitian Hamiltonian systems with unbalanced gain and loss [21,22,23,24,25,26,27,28,29,30,31,32], such as passive (no gain) optical waveguide [21], large optical multilayer structure [22], two-layer slab [23], plasmonic waveguide [24,25,26,27], and metamaterial [28,29,30,31,32]. In 2013, Feng et al [21] experimentally demonstrated unidirectional reflectionlessness in PT symmetry optical waveguide system, where reflection from one port was distinctly diminished.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, unidirectional reflectionless propagations were realized in non-PT symmetry plasmonic waveguide systems based on phase coupling [24,25,26]. Further, Zhang et al [27] realized dual-band unidirectional reflectionlessness based on near-field coupling between a single resonator and the resonant modes of two resonators in a non-Hermitian plasmonic waveguide system. More than that, unidirectional reflectionlessness also can be achieved in metamaterial system.…”
Section: Introductionmentioning
confidence: 99%